Biological and chemical management of diseases of safflower (Carthamus tinctorius L.): BIOLOGICAL AND CHEMICAL MANAGEMENT OF DISEASES OF SAFFLOWER - M SURESH; R D PRASAD; P PADMAVATHI; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2016)
An experiment was carried out to evaluate the efficacy of different bio-agents and chemicals against seed and soil borne diseases of safflower. Significantly low per cent disease incidence was recorded in treatments with bio-agents, Trichoderma harzianum Th4d SC @ 2ml/kg seed (36.8% for Alternaria leaf spot, 26.4% for wilt and 18.3% for blight) and Pseudomonas fluorescens Pf2 WP @5g/kg seed (38.2% for Alternaria leaf spot, 26.4% for wilt and 28.2% for blight), which are on par with chemical treatments. Further, T. harzianum and P. fluorescens seed treatments resulted in higher seed yields (924 kg/ha and 915 kg/ha, respectively) which are statistically at par with chemical treatment, carbendazim + mancozeb @ 0.2% (932 kg/ha).